Influências das condições de torneamento do aço inoxidável supermartensítico nos parâmetros de rugosidade assimetria e achatamento - Igor Alves de Oliveira (2020)
The complexity of oil extraction operations in corrosive environments has required the use of new materials with special characteristics, such as higher mechanical strength associated with higher resistance to corrosion. One of the materials that has gained great prominence in the oil and gas industry is supermartensitic stainless steels, which are steels developed from an improvement in martensitic stainless steels. They are characterized as an intermediate option between martensitic stainless steels and duplex stainless steels considering corrosion resistance and manufacturing cost. The aim of the present work is to investigate the correlation between cutting parameters when turning a supermartensitic stainless steel (CA6NM) class and the roughness parameters, arithmetic mean deviation, asymmetry and flattening. For this purpose, samples were turned using some combinations of cutting parameters: 120m / min and 200m / min for cutting speed and 0.10mm / rot and 0.25mm / rot for the feed. With the aid of an optical profilometer and the contact roughness meter, it was possible to measure these roughness parameters. The results showed that the increase in the cutting speed from 120m / min to 200m / min led to a decrease in the parameters arithmetic mean deviation, asymmetry and flattening of the samples; while the increase in feed from 0.1mm / rot to 0.25mm / rot led to an increase in parameters. This trend in the behavior of the arithmetic mean deviation, asymmetry and flattening parameters was confirmed in both roughness measurement techniques.